Neonatal Polycythemia - Abdurahman Sukadi; Anna Alisjahbana (Indonesian Pediatric Society, 1974)
The purpose of this paper is toreport a case of neonatal polycythe-mia thought to be caused by delayedcord clamping. Maternal-fetal trans-fusion is also a probable cause.